High-throughput screening of transition metal doping and defect engineering on single layer SnS2 for the water splitting hydrogen evolution reaction. Issue 40 (13th September 2022) - Xu, Ruixin; Bo, Tingting; Cao, Shiqian; Mu, Nan; Liu, Yanyu; Chen, Mingyan; Zhou, Wei
Abstract : The HER activity of SnS2 nanosheet with transition metal doping and S vacancy defect was screened through DFT calculations. The modified p z band center combining with a new descriptor φ is proposed to predict the HER activity. Abstract : Doping and defect engineering have been widely used to improve the hydrogen evolution reaction (HER) activity of catalysts. Herein, the improved HER activity of SnS2 nanosheets was systematically investigated. With transition metal (TM) doping, the basal plane S atom can be significantly activated for the HER. The calculated hydrogen adsorption free energy (Δ G H* ) of V, Mn, Ni, and Tc@SnS2 is close to 0 eV. Furthermore, the hollow site of these nanosheets can be easily activated after introducing a S vacancy and these materials need smaller cathode voltage to introduce a S vacancy than pristine SnS2 nanosheets. Surprisingly, Δ G H* can reach 0.06 eV for pristine SnS2 nanosheets by introducing 4.17% S vacancy concentration, which is better than that of platinum (Pt) catalysts. In addition, a corrected p z band center model with a new descriptor φ was proposed for the prediction of HER activity. Our work offers a good understanding of the effects of TM doping and defect engineering on the improvement of HER activity at the atomic level.